A novel image encryption framework using Wireworld cellular automaton and hybrid chaotic maps for enhanced security - Bayan Alabdullah; Hadeel Alsolai; Fatimah Alhayan; Atif Ikram; Abrar Almjally; Mohammad Shehab; Marwan Ali Albahar (PLoS ONE, 2025)
The generation, storage, and transmission of digital images have become ubiquitous in today’s interconnected world. Ensuring the security of these images is a critical challenge that demands immediate attention. This study proposes a novel image encryption algorithm designed to address these concerns effectively. The proposed framework leverages the unique properties of three key constructs: the Wireworld cellular automaton, the 1D logistic chaotic map, and the piecewise linear chaotic map. The 1D logistic chaotic map is employed to generate random numbers, which are used to initialize the Wireworld cellular automaton. The automaton, in turn, introduces scrambling effects into the plaintext image, effectively disrupting its pixel arrangement. Additionally, the piecewise linear chaotic map is utilized to achieve diffusion effects, further enhancing the security of the encryption process. Extensive security analyses and machine experiments have yielded highly promising results. The proposed algorithm has been rigorously evaluated using a variety of validation metrics, including key space analysis, correlation coefficient, Cartesian and polar histograms, information entropy, histogram variance, and peak signal-to-noise ratio (PSNR). In particular, we got an entropy of 7.9975 and histogram variance 251.9867. These metrics collectively demonstrate the algorithm’s strong security characteristics and its resilience against potential attacks. The findings suggest that the proposed image cipher is not only highly secure but also practical for real-world applications. It holds significant potential for safeguarding digital images across diverse domains, including healthcare, military, and multimedia communication. This study underscores the viability of the proposed approach as a reliable solution for ensuring the security of images in an increasingly digital world.